LAPORAN KASUS : PENANGANAN KERATOCONJUNGTIVITIS VERNAL DI RUMAH SAKIT DAERAH KABUPATEN LOMBOK UTARA - Ida Ayu Kirtiasih; Yulia Dewi Suandari; Hasanatul Fitriani (Jurnal Riset Multidisiplin Edukasi, 2025)
Vernal keratoconjunctivitis (VKC) is an allergic eye disease characterized by chronic, bilateral inflammation, most often involving the upper tarsal conjunctiva. VKC is more common in young patients, males, and those in tropical regions. Patients with VKC often present with symptoms of severe itching, redness, and watery eyes. This case report describes a 10-year-old boy who presented with complaints of red and swollen eyes for the past week. The patient also reported pain and glare when exposed to light. He felt extremely itchy, often rubbing his eyes. Anterior segment examination revealed hyperemia in both eyes, ciliary and conjunctival injection, cobblestone lesions on the superior tarsal conjunctiva, and transtas dots in both eyes. The patient was treated with prednisone eye drops (4 x 1 drop ODS), levofloxacin antibiotic eye drops (6 x 1 drop ODS), and sodium chloride + potassium chloride eye drops (6 x 1 drop ODS).